Does a research article’s country of origin affect perception of its quality and relevance? A national trial of US public health researchers. - Harris,MJ; Macinko,J; Jimenez,G; Mahfoud,M; Anderson,C (BMJ Open, 2015)
Objectives The source of research may influence one's interpretation of it in either negative or positive ways, however, there are no robust experiments to determine how source impacts on one's judgment of the research article. We determine the impact of source on respondents’ assessment of the quality and relevance of selected research abstracts.Design Web-based survey design using four healthcare research abstracts previously published and included in Cochrane Reviews.Setting All Council on the Education of Public Health-accredited Schools and Programmes of Public Health in the USA.Participants 899 core faculty members (full, associate and assistant professors)Intervention Each of the four abstracts appeared with a high-income source half of the time, and low-income source half of the time. Participants each reviewed the same four abstracts, but were randomly allocated to receive two abstracts with high-income source, and two abstracts with low-income source, allowing for within-abstract comparison of quality and relevancePrimary outcome measures Within-abstract comparison of participants’ rating scores on two measures—strength of the evidence, and likelihood of referral to a peer (1–10 rating scale). OR was calculated using a generalised ordered logit model adjusting for sociodemographic covariates.Results Participants who received high income country source abstracts were equal in all known characteristics to the participants who received the abstracts with low income country sources. For one of the four abstracts (a randomised, controlled trial of a pharmaceutical intervention), likelihood of referral to a peer was greater if the source was a high income country (OR 1.28, 1.02 to 1.62, p<0.05).Conclusions All things being equal, in one of the four abstracts, the respondents were influenced by a high-income source in their rating of research abstracts. More research may be needed to explore how the origin of a research article may lead